Predictors of Parenting Stress Trajectories in Premature Infant–Mother Dyads - Spinelli, Maria (J Fam Psychol, 2013)
This prospective longitudinal study examined predictors of parenting stress trajectories over time in a sample of 125 mothers and their preterm infants. Infant (multiple birth, gestational age, days hospitalized, and neonatal health risks) and maternal (socioeconomic, education, depressive symptoms, social support, and quality of interaction during infant feeding) characteristics were collected just prior to infant hospital discharge. Parenting stress and maternal interaction quality during play were measured at 4, 24, and 36 months corrected age. Hierarchical linear modeling was used to analyze infant and maternal characteristics as predictors of parenting stress scores and change over time. Results indicated significant variability across individuals in parenting stress at 4 months and in change trajectories. Mothers of multiples and infants with more medical risks and shorter hospitalization, and mothers with lower education and more depressive symptoms, reported more parenting stress at 4 months of age. Parenting stress decreased over time for mothers of multiples and for mothers with lower education more than for mothers of singletons or for mothers with higher educational levels. Changes in parenting stress scores over time were negatively associated with maternal behaviors during mother–infant interactions. Results are interpreted for their implications for preventive interventions.